The practical bioinformatician - Wong, Limsoon, 1965- (World Scientific Pub. Co., 2004)
Computer scientists have increasingly been enlisted as "bioinformaticians" to assist molecular biologists in their research. This book is a practical introduction to bioinformatics for these computer scientists. The chapters are in-depth discussions by expert bioinformaticians on both general techniques and specific approaches to a range of selected bioinformatics problems. The book is organized into clusters of chapters on the following topics:. Overview of modern molecular biology and a broad spectrum of techniques from computer science - data mining, machine learning, mathematical modeling